2019
DOI: 10.1007/s00167-019-05560-w
|View full text |Cite
|
Sign up to set email alerts
|

Every second retired elite female football player has MRI evidence of knee osteoarthritis before age 50 years: a cross-sectional study of clinical and MRI outcomes

Abstract: Purpose To assess knee health in retired female football players, using magnetic resonance imaging (MRI) and self‐report. The focus of analysis were degenerative changes of the tibiofemoral joint, and their relationship to osteoarthritis symptoms and previous knee injury. Methods Forty‐nine retired elite, female football players (98 knees) aged 37 years on average participated. Tibiofemoral cartilage and meniscus status of both knees were evaluated using MRI and graded according to modified Outerbridge and Sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 43 publications
(64 reference statements)
2
28
0
1
Order By: Relevance
“…Historically, injury incidence has been high in women's football [2] and remains so today [3]. It is expected that female footballrelated injuries and longer-term wellbeing will become a significant topic in sports medicine as evidenced by several recent publications [4][5][6]. A recent systematic review also suggested that recreational football practice is medicineit is beneficial for cardiovascular and bone health, body composition, type 2 diabetes, and prostate cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, injury incidence has been high in women's football [2] and remains so today [3]. It is expected that female footballrelated injuries and longer-term wellbeing will become a significant topic in sports medicine as evidenced by several recent publications [4][5][6]. A recent systematic review also suggested that recreational football practice is medicineit is beneficial for cardiovascular and bone health, body composition, type 2 diabetes, and prostate cancer [7].…”
Section: Introductionmentioning
confidence: 99%
“…Of the 22 included records, 16 studies had a cross-sectional design, four were case-control studies [ 24 – 26 , 51 ] and two cohort studies [ 35 , 36 ]. Two studies were from the United States [ 40 , 50 ] and one from South Korea [ 53 ] but the majority was conducted in Europe: Germany ( n = 6, Federal Republic of Germany ( n = 4) [ 38 , 45 , 46 , 51 ], German Democratic Republic ( n = 2) [ 43 , 44 ]), Denmark ( n = 3) [ 8 , 17 , 36 ], United Kingdom ( n = 3) [ 24 – 26 ], Finland ( n = 2) [ 27 , 35 ], Czech Republic ( n = 1) [ 42 ], Netherlands ( n = 1) [ 39 ], Russia ( n = 1) [ 37 ], Slovenia ( n = 1) [ 41 ] and Sweden ( n = 1) [ 47 ]. The year of study publication ranged from 1962 to 2020.…”
Section: Resultsmentioning
confidence: 99%
“…Most studies ( n = 14) involved only male participants, four studies [ 24 , 35 , 52 , 53 ] recruited both sexes and one study [ 46 ] included only females. Three studies did not provide any information about the sex of participants, but we presumed that they were predominantly male, as in two studies which investigated professional football players there was no professional women’s league at time of recruitment [ 39 , 41 ], or due to the nature of the described occupation (manual welders in ship-building) [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…One article suggests that physical load from sports may put women at risk for development of severe hip osteoarthrosis [16]. Another study found over half of retired elite female soccer players have osteoarthritis and meniscus tears [17]. There is also high prevalence of hip and knee osteoarthritis arthroplasty among former elite male athletes [18].…”
Section: Future Implicationsmentioning
confidence: 99%